2023
DOI: 10.1002/adfm.202309256
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria Toxoid Particles as Q Fever Vaccine

Gayathri Sam,
Shuxiong Chen,
Karren Plain
et al.

Abstract: There is an unmet need for a stable and nonreactogenic vaccine against the bioterrorism agent, Coxiella burnetii, causing Q fever. Here a safe, effective, and non‐reactogenic Q fever vaccine is developed by employing self‐assembled particles (CPs) composed of cross‐reacting material 197, a nontoxic variant of diphtheria toxin. CPs are designed that incorporate selected C. burnetii antigens and assemble them inside engineered Escherichia coli at high yields. A cost‐effective manufacturing process enables the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Similar thermostability studies with BPbased vaccines against COVID-19, group A Streptococcus, and Q Fever also demonstrated the stability of BP-based vaccines in terms of protein profiles, protein band intensity, particle sizes, and zeta potentials at different temperatures. [26,45,46] Moreover, enzyme-linked immunosorbent assay (ELISA) results confirmed that the antigenicity of these BP particles was not jeopardized after incubation at different temperatures ranging from 4 °C to 56 °C for 4 weeks. [26,45,46] We additionally developed modified BPs coated with the NP366 (NT68) epitope derived from the influenza A strain A/NT/60/68 (H3N2) and the PA 224 epitope in order to utilize F5 CD8 + T cells, which are TCR transgenic CD8 + T cells specific for the influenza A virus nucleoprotein epitope from the strain A/NT/60/68 (H3N2), for in vitro and in vivo T cell proliferation studies.…”
Section: Design Production and Characterization Of The Bp-np 366 /Pa ...mentioning
confidence: 88%
See 1 more Smart Citation
“…Similar thermostability studies with BPbased vaccines against COVID-19, group A Streptococcus, and Q Fever also demonstrated the stability of BP-based vaccines in terms of protein profiles, protein band intensity, particle sizes, and zeta potentials at different temperatures. [26,45,46] Moreover, enzyme-linked immunosorbent assay (ELISA) results confirmed that the antigenicity of these BP particles was not jeopardized after incubation at different temperatures ranging from 4 °C to 56 °C for 4 weeks. [26,45,46] We additionally developed modified BPs coated with the NP366 (NT68) epitope derived from the influenza A strain A/NT/60/68 (H3N2) and the PA 224 epitope in order to utilize F5 CD8 + T cells, which are TCR transgenic CD8 + T cells specific for the influenza A virus nucleoprotein epitope from the strain A/NT/60/68 (H3N2), for in vitro and in vivo T cell proliferation studies.…”
Section: Design Production and Characterization Of The Bp-np 366 /Pa ...mentioning
confidence: 88%
“…[26,45,46] Moreover, enzyme-linked immunosorbent assay (ELISA) results confirmed that the antigenicity of these BP particles was not jeopardized after incubation at different temperatures ranging from 4 °C to 56 °C for 4 weeks. [26,45,46] We additionally developed modified BPs coated with the NP366 (NT68) epitope derived from the influenza A strain A/NT/60/68 (H3N2) and the PA 224 epitope in order to utilize F5 CD8 + T cells, which are TCR transgenic CD8 + T cells specific for the influenza A virus nucleoprotein epitope from the strain A/NT/60/68 (H3N2), for in vitro and in vivo T cell proliferation studies. Characterization of these particles confirmed that they were similar to the BP-NP 366 /PA 224 with regards to size, composition, and thermostability (Figures S4-S7, Supporting Information).…”
Section: Design Production and Characterization Of The Bp-np 366 /Pa ...mentioning
confidence: 91%
“…Ybgf has been found to be one of the most important immunodominant antigens in humans and laboratory animals, as well as one of the most promising candidates for future applications in serodiagnosis and vaccinology ( Bach et al, 2023 ; Jiao et al, 2014 ; Sam et al, 2023 ). This periplasmic protein is considered a specific marker of PhII (acute infection).…”
Section: Discussionmentioning
confidence: 99%